What has changed in the attitude of health workers towards vaccination after the pandemic COVID-19 - S. M. Kharit; L. V. Romanov; Yu. E. Konstantinova; S. A. Bogdan (Журнал инфектологии, 2024)
The attitude towards vaccination of medical workers has been studied repeatedly. After active campaigning for vaccination during the pandemic, there was a decrease in confidence in vaccinations in general.The aim of the work was analysis of the attitudes of medical workers towards vaccination, the effectiveness and safety of vaccines against various conditions in 2024 yMaterials and methods. In the online survey site www. meta.gcgie.ru in the period from 1.04.2024 to 1.06.2024 (2 calendar months).1,508 people took part, 91.6% women. By profession, out of 1033 respondents there were: 525 nurses (50.8%),156 therapists (15.1%), pediatricians – 115 (11.1%), surgeons 96 (9.3%), epidemiologists 41 (4.0%),. The questionnaire included 50 questions with 513 possible answers. Statistical processing of the survey results was carried out using a BIsystem:Results. Out of 1045 respondents, 832 treat vaccinations positively (79,6%), 142 (13,6%) – neutrally, cautiously – 60 (5.7%) and negatively – 12 (1.1%), 25.1% of respondents (264 out of 1051) believe that it is better to get over some infections than to be vaccinated. There is a significant difference between confirming the answer about the need for vaccination and vaccinating yourself, as well as evaluating the effectiveness of the vaccine (even for measles vaccines, 90.7% say they need to be vaccinated, only 83.5% are vaccinated and only 76.7% are confident in the effectiveness of the vaccine. Only 49.9% (525 out of 1,053 responses) believed that vaccines against infections not included in the national vaccination calendar were necessary. The lack of confidence in the safety of vaccines is manifested in the fact that doctors associate vaccinations with the development of cerebral palsy, oncology (10.7% each), autoimmune diseases (38.3%), epilepsy (12.0%). Doctors named unsafe vaccines (83.7% – 881 out of 1052 responses), inefficiency (24.3% 256 out of 1052), no need for vaccinations at all (14.5% 157 out of 1052), religious reasons (38.4% 404 out of 1052 responses) as the reasons for patients’ refusal of vaccination. To improve the work on vaccination, 44.5% indicated the need for information on the official websites of the Ministry of Health of the Russian Federation, FMBA, Rospotrebnadzor and RoszdravnadzorConclusion The results of the survey indicate the need to modernize the system of training in vaccination of medical workers of various specialties, the development of new forms of information presentation, the use of official websites, the development of algorithms for communicating with the population on adherence to vaccination,